A feasible approach to synthesize Cu2O microcrystals and their enhanced non-enzymatic sensor performance1. Issue 73 (9th August 2015) - Liu, Xinmei; Sui, Yongming; Yang, Xinyi; Jiang, Lina; Wang, Fei; Wei, Yingjin; Zou, Bo
<x xml:space="preserve">Abstract</x> This work provides a green and feasible approach to obtain a "clean surface" Cu2O with enhanced glucose sensor performance.